Endurance Training Counteracts the High-Fat Diet-Induced Profiling Changes of ω-3 Polyunsaturated Fatty Acids in Skeletal Muscle of Middle-Aged Rats - Li, Ting; Ruan, Ding-Guo; Lin, Zhen-Mao; Liu, Tai-Yang; Wang, Kou; Xu, Xiao-Yang; Duan, Rui (Frontiers in Physiology, 2019)
Purpose: To investigate the effects of endurance training on the content of ω-3 polyunsaturated fatty acids (PUFAs) and their distribution among lipid classes in skeletal muscle in middle aged, high-fat diet fed rats. Method: Thirty 10-month old male Sprague Dawley (SD) rats were assigned to four groups. Two groups of rats remained sedentary and were fed chow diet (C group), or High-Fat Diet (H group), respectively. The other two groups of rats were subjected to endurance training while maintaining their chow diet (EC group), or high-fat diet (EH group). After 16 weeks endurance training and/or diet intervention, the content of ω-3 PUFAs and ω-3 PUFA-containing lipids in rat soleus muscle were analyzed by lipidomics. Results: Rats fed a high-fat diet exhibited decreased overall amount of ω-3 PUFAs in soleus muscle, while endurance training preserved the total amount of ω-3 PUFAs. Both the endurance training and high-fat diet alone changed the profiles of ω-3 PUFAs in different lipid classes. Specifically, the amount of Triacylglycerol (TG), Lysophosphatidylcholine (LPC), Phosphatidylcholine (PC) and Phosphatidylglycerol (PG) containing ω-3 PUFAs in soleus muscle was increased by endurance training, but the amount of Lysophosphatidylenthanol (LPE), Lysophosphatidylinositol (LPI), Lysophosphatidylserine (LPS), Cardiolipin (CL), Phosphatidic acid (PA) and Phosphatidylinositol (PI) was decreased. The high-fat diet induced a decrease of ω-3 PUFAs in TG, LPE, LPS, CL, Platelet activating foctor (PAF), PC, PE and PS, and an increase in LPC, LPI, PA and Phosphatidylglycerol (PG). In addition, the effects of the endurance training on ω-3 PUFAs in skeletal muscle was also evident in high-fat diets fed rats, which counteracts the profiling changes caused by high-fat diet feeding. Conclusion: The beneficial effects of endurance training on skeletal muscle may be achieved to some extent through recovering the content of ω-3 PUFAs that has been decreased by high-fat diet feeding.